Building a world class civil service for twenty-first century India - "Das, S.K" (New Delhi, 2011)
Today, India is one of the leading players on the global stage. It is competing with other countries not just in the marketplace but also in respect of its governance structures. This book underscores the need for creating a modern civil service, which epitomizes best practices overseas and in the private sector, and exemplifies contemporary management philosophy and techniques. Using a comparative approach, S.K. Das identifies a range of initiatives that will serve to transform the civil service into a world-class organization, compatible with strategic, economic, and technological requirements of the twenty-first century. Based on the reform experiences of Australia, New Zealand, Sweden, and the UK, these initiatives have been carefully modulated to suit India's requirements. Underlining the challenges involved in reforming the bureaucracy, the author also discusses the legislative, administrative, and procedural changes necessary to build a high-performing civil service.
Keywords: "Civil service reform, Public administration-India"